Perceived Aetiology of Addiction and Stigmatizing Attitudes of Mental Health Professionals towards Substance Use Disorders Patients - Sara Ishaq, Nashi Khan, Faiza Khalid, (Pakistan Journal of Medical & Health Sciences, 2023)
Purpose: The study aimed to investigate the relationship between aetiological beliefs and stigmatizing attitudes of mental health professionals towards substance use patients. It was hypothesized that bio-genetic causal attributions would have a positive relationship with stigmatizing attitudes whereas psycho- social causal attributions would have a negative relationship with stigmatizing attitudes. Method: Correlational research design and purposive sampling strategy was used to collect a sample of 100 mental health professionals (MHPs) both from government hospitals and private addiction centres. Results: Results showed that Bio- genetic causal attributions had a positive relationship with stereotypic attitudes, treatment pessimism and non- permissiveness, however, no significant relationship was observed with moralism and treatment intervention. Also, psycho- social causal attributions had a positive relationship with stereotypic attitudes and moralism whereas no significant relationship was present with treatment pessimism, non- permissiveness and treatment intervention. Conclusion: The study highlights the multifaceted nature of stigma therefore the importance of combined aetiological information in anti- stigma interventions and empirically informed curriculum to reduce stigmatizing attitudes of mental health professionals. Keywords: Perceived Aetiology, Therapeutic Attitudes, Stigmatizing Attitudes, Substance Use Disorders